(untitled) (Research, Society and Development, 2022)
Knowledge about the biology and behavior of termites considered urban pests is still incipient. In this sense, this study aimed to evaluate the natural resistance of cupiúba (Goupia glabra Aubl.), guariúba (Clarisia racemosa Ruiz & Pav.) and marupá (Simaruba amara Aubl.) wood, important commercial Amazonian species, to termite attack. To this end, experiments were carried out in three areas on the University Campus of the Federal University of Amazonas, considered the third urban forest fragment in the world. At first, corrugated cardboard baits were installed to identify areas of termite activity. The baits were randomly buried for a period of 80 days, being later removed for visual inspection. At points with confirmed foraging activity, specimens (30 x 2 x 2 cm) of the three wood species were installed. In each experimental area, 12 specimens of each forest species were buried, totaling 108 bodies. The specimens were removed from the soil in two evaluation periods: 90 and 120 days. The results were submitted to Analysis of Variance (ANOVA). Statistical differences were identified at p<0.05 for wood consumption (g), with the species with the lowest density (marupá: 0.40 g cm–3) being the most susceptible to attack. In total, 55% of the specimens were infested by termites of the genus Nasutitermes (N. corniger and N. surinamensis) and Cornitermes (C. acignathus). These results corroborate that the wood density impacts the natural resistance to the attack of xylophagous insects and can contribute for the prevention and control methods to be properly planned.